Relationship between Energy Intake Levels and Physical Activity with the Incidence of Obesity in Elementary School Age Children in Semarang City - Agina, Grace; Sundari, Santy; Sudrajat, Agus (Indonesian Journal of Nutrition Science and Food, 2024)
Obesity is the impact of excess energy intake compared to energy expenditure, so excess energy is stored in the form of fat in the body. The cause of obesity is influenced by an unbalanced diet and low/lack of physical activity. This study aims to determine the relationship between energy intake and physical activity levels with obesity in elementary school children in Semarang. This type of research is a quantitative correlational study with a cross-sectional approach. The instruments used were a 2x24-hour food recall questionnaire and a 2x24-hour physical activity recall without being consecutive. The population of this study was all elementary school children in the city of Semarang. 75 samples were taken using a purposive random sampling technique. The dependent variable in this study was obesity, while the independent variables were the level of energy intake and physical activity. The data were tested using bivariate analysis with the Chi-Square test to determine the relationship between energy intake and physical activity levels with the incidence of obesity, while multivariate analysis used the Pearson Correlation test with SPSS software. The results showed that there was a significant relationship between energy intake and physical activity levels with the incidence of obesity in elementary school children in the city of Semarang.